Tantangan dan Manajemen Kinerja Generasi Z di Indonesia - Br Sibagariang, Oktaviana Gracella; Tarigan, Miska Irani (Magister Manajemen Universitas Wisnuwardhana, 2025)
Generation Z, born between the mid-1990s and early 2010s, increasingly dominates the global workforce. Their unique characteristics, such as reliance on technology, preference for work flexibility, and high expectations for work-life balance, present new challenges in performance management. This study explores the key challenges in managing the performance of Generation Z as well as strategies that organizations can implement to optimize their productivity and engagement. By using a literature review research method, this research identifies that a transparent management approach, real-time feedback, and sustainable career development are key factors in the successful performance management of Generation Z. These findings are expected to provide insight for managers and organizational leaders in developing more adaptive and effective strategies in managing the workforce of this generation.